Adapted Tango to improve blood inflammatory markers in middle‐aged African‐American female caregivers of persons with Alzheimer's disease: A clinical trial. (31st December 2021) - Wharton, Whitney; Jeong, Leanne; Ni, Liang; Bay, Allison A; Shin, Ryan; McCullough, Lauren; Silverstein, Hayley; Hart, Ariel R; Swieboda, Dominika; Hu, William T; Hackney, Madeleine E
Abstract: Background: Alzheimer's disease (AD) is a devastating, progressive neurodegenerative disease resulting in memory loss and a severe reduction in ability to perform activities of daily living. Ethnicity‐related genetic factors promoting the development of dementias among African Americans (AA) and increased risk among females for developing AD indicates that AA female with a parent with AD are at great risk for developing dementias. Method: This phase I study assessed the impact of a 12 week, 20‐lesson adapted Argentine Tango intervention (N=24) vs. a no‐contact control group (N=10) on measures of cognition, motor and psychosocial performance, and plasma inflammatory markers in middle‐aged (45‐65 years) AA females who are at increased risk for AD by virtue of parental history. Result: Some females (n=17) were also caregivers, and thus the impact of the program on caregiving burden was examined in this subset. Preliminary analysis of efficacy was conducted with significance tests on biomarkers and key measures of balance, strength, and cognition, including visuospatial and executive function. After 12 weeks, Tango participants had significantly decreased inflammatory cytokine levels: IL‐7 (p=.003), IFN‐γ (p=.011), and TNFα (p=.011), compared to controls. Participants in Tango improved on the Fullerton Advanced Balance Scale, which measures both dynamic and static balance (p=.023), the 30 second chair stand, which assesses functional lower body strength in older adults (p=.018), and inhibition of the color word interference test, which measures to ability to inhibit cognitive interference (p=0.031). Large effects were noted for the Tango group from pre to postintervention in the Trails B test score, which measures executive control and functioning. Other non‐significant, yet large effects were noted in gait speed, spatial cognition, and executive function. Moderate effects were noted in caregiving burden measures among the subset of caregivers. Conclusion: These data show substantial cognitive and motor improvements and reduction in inflammatory biomarkers through a non‐pharmacologic and affordable intervention among a small cohort of AA females with a parental history of AD.